VIRTUAL PARALLEL ENVIRONMENT USING PVM CASE STUDY BUBBLE SORT ALGORITHM - Pratama, Iwan (PROXIES, 2017)
Parallel computing is a technique to solve a problem using many CPUs. To perform parallel computing, it requires parallel computer, which is commonly known as supercomputer or multiprocessor computer. Nowadays, a supercomputer is still very expensive. Therefore, parallel algorithm is difficult to be applied in general. To resolve this problem, virtual parallel workstation is created. Virtual parallel workstation is a network of computers controlled by a program that can regulate the allocation of computational processes to processors across the entire network. This project uses PVM (Parallel Virtual Machine) to implement the parallel workstation environment to perform Bubble Sort Algorithm in parallel approach